ANALISIS PENGENDALIAN NYALA LAMPU RUMAH DENGAN MENGGUNAKAN ANDROID SMARTPHONE BERBASIS MIKROKONTROLER ATMEGA 8535 - RAHMAD HIDAYAT; Agung Rahman Wibowo (Jurnal Online Sekolah Tinggi Teknologi Mandala, 2014)
Android is operation system that available as open source, so that we as user can give our contribution to develops operation system which has widespread user around the world. We can develops Android as many function, for example as lamp control using Android. Communication that we uses is Bluetooth feature, which is already embedded in Android system, whereas it will communicated with microcontroller to control dimmer circuit. Dimmer circuit itself is lamp brightness control circuit, that works as cutting signal using the function of TRIAC. Method that used in the developing communication between Android and Microcontroller is action method, where we directly testing the theory of communication between Android and Microcontroller, are communication can happen between two device. From the result of testing communication between Android and Microcontroller, we can concludes that communication between Android and Microcontroller can happen through Bluetooth as mediator, with transmission distance 20-30 metre, through serial communication. In the future, we can take advantage from cloud computing technology, which is already used in widespread field, so our hopes that this technology can be access anywhere will be come true.